Determinants of outcomes following surgery for type A acute aortic dissection: the UK National Adult Cardiac Surgical Audit. (1st September 2021) - Benedetto, Umberto; Dimagli, Arnaldo; Kaura, Amit; Sinha, Shubhra; Mariscalco, Giovanni; Krasopoulos, George; Moorjani, Narain; Field, Mark; Uday, Trivedi; Kendal, Simon; Cooper, Graham; Uppal, Rakesh; et al.
Abstract: Aims : Operability of type A acute aortic dissections (TAAAD) is currently based on non-standardized decision-making process, and it lacks a disease-specific risk evaluation model that can predict mortality. We investigated patient, intraoperative data, surgeon, and centre-related variables for patients who underwent TAAAD in the UK. Methods and results: We identified 4203 patients undergoing TAAAD surgery in the UK (2009–18), who were enrolled into the UK National Adult Cardiac Surgical Audit dataset. The primary outcome was operative mortality. A multivariable logistic regression analysis was performed with fast backward elimination of variables and the bootstrap-based optimism-correction was adopted to assess model performance. Variation related to hospital or surgeon effects were quantified by a generalized mixed linear model and risk-adjusted funnel plots by displaying the individual standardized mortality ratio against expected deaths. Final variables retained in the model were: age [odds ratio (OR) 1.02, 95% confidence interval (CI) 1.02–1.03; P  < 0.001]; malperfusion (OR 1.79, 95% CI 1.51–2.12; P  < 0.001); left ventricular ejection fraction (moderate: OR 1.40, 95% CI 1.14–1.71; P  = 0.001; poor: OR 2.83, 95% CI 1.90–4.21; P  < 0.001); previous cardiac surgery (OR 2.29, 95% CI 1.71–3.07; P  < 0.001); preoperative mechanical ventilation (OR 2.76, 95% CI 2.00–3.80; P  < 0.001); preoperative resuscitation (OR 3.36, 95% CI 1.14–9.87; P  = 0.028); and concomitant coronary artery bypass grafting (OR 2.29, 95% CI 1.86–2.83; P  < 0.001). We found a significant inverse relationship between surgeons but not centre annual volume with outcomes. Conclusions : Patient characteristics, intraoperative factors, cardiac centre, and high-volume surgeons are strong determinants of outcomes following TAAAD surgery. These findings may help refining clinical decision-making, supporting patient counselling and be used by policy makers for quality assurance and service provision improvement. Graphical Abstract: